2014
DOI: 10.1021/jm500075d
|View full text |Cite
|
Sign up to set email alerts
|

Bis-alkylamine Indolo[3,2-b]quinolines as Hemozoin Ligands: Implications for Antimalarial Cytostatic and Cytocidal Activities

Abstract: To get insight into the relevance of targeting hemozoin (Hz) crystals, two isomeric series, N5,N10-bis-alkylamine (2a-k) and N10,O11-bis-alkylamine (3a-k) indolo[3,2-b]quinolines, were evaluated for their in vitro activity against chloroquine (CQ)-resistant and sensitive strains of Plasmodium falciparum. In general, compounds of series 3 were more active than isomers 2, with IC50/LD50 ranging from 25/233 nM (3i) to 1.3 (3a)/10.7 (3b) μM. SAR analyses showed that lipophilicity and chlorine substitution at C3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…[23] Malarial parasites ingest and digest >70% of host hemoglobin as an amino acid source inside erythrocytes, and hemoglobin degradation, as well as hemozoin formation, are essential for parasite survival, making these processes important targets for antimalarials development. [24] Indole derivatives could exert antimalarial activity through different mechanisms of action including hemoglobin degradation and hemozoin formation, [25] so indole derivatives possess potential activity against both drug-sensitive and Abbreviations: CC 50 , half-maximal cytotoxicity concentration; CQS, chloroquine-sensitive; CQR, chloroquine-resistant; HCV, hepatitis virus C; HIV, human immunodeficiency virus; IC 50 , halfmaximal inhibitory concentration; MDR, multidrug-resistant; P. falciparum, Plasmodium falciparum; P. knowlesi, Plasmodium knowlesi; P. malariae, Plasmodium malariae; P. ovale, Plasmodium ovale; P. vivax, Plasmodium vivax; SAR, structure-activity relationship; SI, selectivity index; RI, resistance index; WHO, World Health Organization.…”
mentioning
confidence: 99%
“…[23] Malarial parasites ingest and digest >70% of host hemoglobin as an amino acid source inside erythrocytes, and hemoglobin degradation, as well as hemozoin formation, are essential for parasite survival, making these processes important targets for antimalarials development. [24] Indole derivatives could exert antimalarial activity through different mechanisms of action including hemoglobin degradation and hemozoin formation, [25] so indole derivatives possess potential activity against both drug-sensitive and Abbreviations: CC 50 , half-maximal cytotoxicity concentration; CQS, chloroquine-sensitive; CQR, chloroquine-resistant; HCV, hepatitis virus C; HIV, human immunodeficiency virus; IC 50 , halfmaximal inhibitory concentration; MDR, multidrug-resistant; P. falciparum, Plasmodium falciparum; P. knowlesi, Plasmodium knowlesi; P. malariae, Plasmodium malariae; P. ovale, Plasmodium ovale; P. vivax, Plasmodium vivax; SAR, structure-activity relationship; SI, selectivity index; RI, resistance index; WHO, World Health Organization.…”
mentioning
confidence: 99%
“…As expected, no cross-resistance of the proposed compounds with quinolone-type anti-malarials is foreseeable, as the calculated RIs for Dd2 and 3D7 were ≅1 (Table 1 ), which is considerably lower than the RI determined for CQ (21.5) [ 20 , 68 ].…”
Section: Discussionmentioning
confidence: 80%
“…The antiplasmodial SAR of indolo[3,2‐b]quinolines 88 (Figure ) showed that chloro at R 1 and R 2 positions improved the antiplasmodial activity against CQS 3D7 and CQR W2 strains, and hybrids with alkylamino at R 3 position were more potent than the corresponding cycloalkylamino analogs . The RI of the hybrids was 0.3‐0.7, demonstrating their potency to treat drug‐resistant malaria.…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%